2000
DOI: 10.1016/s0014-5793(00)01907-4
|View full text |Cite
|
Sign up to set email alerts
|

The phytotoxic lichen metabolite, usnic acid, is a potent inhibitor of plant p‐hydroxyphenylpyruvate dioxygenase

Abstract: The lichen secondary metabolite usnic acid exists as a (3 3) and a (+) enantiomer, indicating a K K or L L projection of the methyl group at position 9b, respectively. (3 3)-Usnic caused a dose-dependent bleaching of the cotyledonary tissues associated with a decrease of both chlorophylls and carotenoids in treated plants whereas no bleaching was observed with the (+) enantiomer. (3 3)-Usnic acid inhibited protophorphyrinogen oxidase activity (I 50 = 3 W WM), but did not lead to protoporphyrin IX accumulation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 17 publications
2
79
0
1
Order By: Relevance
“…In all photosynthetic organisms, HPPD also plays an anabolic role, as HGA is essential for the formation of isoprenoid redox molecules such as plastoquinone and tocochromanols (1,2). Plant HPPD is the molecular target of several natural compounds (3,4) and of a range of very effective synthetic herbicides that are currently used commercially (5)(6)(7)(8)(9). In mammals, inborn defects in this pathway give rise to metabolic disorders of different degrees of severity (5,10).…”
Section: -Hydroxyphenylpyruvate Dioxygenase (Hppd)mentioning
confidence: 99%
“…In all photosynthetic organisms, HPPD also plays an anabolic role, as HGA is essential for the formation of isoprenoid redox molecules such as plastoquinone and tocochromanols (1,2). Plant HPPD is the molecular target of several natural compounds (3,4) and of a range of very effective synthetic herbicides that are currently used commercially (5)(6)(7)(8)(9). In mammals, inborn defects in this pathway give rise to metabolic disorders of different degrees of severity (5,10).…”
Section: -Hydroxyphenylpyruvate Dioxygenase (Hppd)mentioning
confidence: 99%
“…( ()-Usnic enantiomer has a greater phytotoxic activity, bleaches the cotyledonary tissues of cucumber seedlings and induces the decrease in chlorophyll and carotenoids in lattuce seedlings more than (')-usnic acid (Romagni et al 2000). As membrane leakage depends on light, the destabilization of the photosynthetic apparatus has been correlated to the irreversible inhibition by both (()-usnic acid (IC 50 0 70 nM) and (')-usnic acid (one order of magnitude less active) of the p-hydroxyphenylpyruvate dioxygenase (HPPD), which catalyzes the synthesis of plastoquinone (PQ): This process stops the synthesis of carotenoids, which usually quench excess photoexcitation energy, and increases the susceptibility of chlorophyll and membranes to degradative processes driven by highly reactive singlet oxygens (Romagni et al 2000).…”
Section: Do Mycorrhizal Fungi Mediate the Effects Of Terricolous Lichmentioning
confidence: 99%
“…As membrane leakage depends on light, the destabilization of the photosynthetic apparatus has been correlated to the irreversible inhibition by both (()-usnic acid (IC 50 0 70 nM) and (')-usnic acid (one order of magnitude less active) of the p-hydroxyphenylpyruvate dioxygenase (HPPD), which catalyzes the synthesis of plastoquinone (PQ): This process stops the synthesis of carotenoids, which usually quench excess photoexcitation energy, and increases the susceptibility of chlorophyll and membranes to degradative processes driven by highly reactive singlet oxygens (Romagni et al 2000). Moreover, the inhibition of photosynthetic electron transport by usnic acid has been observed in illuminated mesophyll cell protoplasts from Commelina sativa (usnic acid 4 mM) (Vavasseur et al 1991) and in isolated chloroplasts from Spinacia oleracea (Inoue et al 1987;Endo et al 1998), Quercus rotundifolia (Oru´s et al 1981) and Lycopersicum esculentum (Latkowska et al 2006): the electron flow has been indicated to be blocked at the oxidizing side of P680 of PSII due to usnic binding to the secondary electron donor (Inoue et al 1987); inhibition of the electron flow by chelating manganese divalent ions and by disturbing the electron flow from the water-splitting catalytic centre to PSII has also been suggested to predispose chlorophylls to photoinhibitory damage as a manganese supply has reversed the inhibition in some experiments (Oru´s et al 1981), but this phenomenon has not always been observed (Vavasseur et al 1991).…”
Section: Do Mycorrhizal Fungi Mediate the Effects Of Terricolous Lichmentioning
confidence: 99%
“…FD, Ferredoxin; FNR, ferredoxin-NADP + reductase; OEC, oxygen-evolving complex; PC, plastocyanin; Pi, inorganic phosphate; PQ, plastoquinone; PQH 2 , reduced PQ. (Romagni et al, 2000b;Meazza et al, 2002), although sorgoleone has other target sites that appear to be more important for its phytotoxicity .…”
Section: Tyr Aminotransferasementioning
confidence: 99%